A Theoretical Analysis of Using Non-Literal Idiomatic Expressions in Communication - Mukhalad Malik; Aras Abdalkarim (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The current paper is an attempt to verify and demonstrate the significance of the use of non-literal idiomatic expressions in communication within a theoretical framework. Being an essential part of the use of language, the paper shows that the use of such idiomatic expressions is vital in various communicative situations due to a lot of reasons. This is achieved throughout the paper by mainly focusing on the linguistic level through which the idiomatic expressions of non-literal use are realized. Then, it shows the various possible meanings, ideas and messages which they may convey through the various linguistic forms in which they are reflected (such as phrases, fixed idioms, proverbs and so on). Finally, the paper sheds light on the significance of the use of those expressions in communication throughout demonstrating the fact that they are actually used in daily life communication and the major role they play in influencing the entire communication event.